Does Sinusitis Affect Lateralization of a Tuning Fork Weber Test?. Issue 6 (July 2021) - Ungar, Omer J.; Wengier, Anat; Cavel, Oren; Abergel, Avraham; Safadi, Ahmad; Warshavsky, Anton; Horowitz, Gilad; Handzel, Ophir; Oron, Yahav; Shilo, Shahaf
Abstract : Objective: To describe the effect of sinusitis on Weber test lateralization which normally lateralizes toward the ear of a conductive hearing loss and away from the ear of a sensorineural hearing loss; to investigate whether the presence of an extra-aural condition might affect Weber test results. Study Design: Descriptive study. Setting: Tertiary referral center. Subjects and Methods: Consecutive adult patients with maxillary and/or frontal sinusitis were included (study group), as well as patients with normal sinus structure and function (control group) were enrolled between February and September 2019. Presence or absence of paranasal disease and middle ear aeration was confirmed by computerized tomography. Subjects with otologic condition were excluded. The physical examinations, tympanograms, and audiograms were unremarkable. The Weber test consisted of 512, 1024, and 2048 Hz tuning forks that were applied on the central incisors and frontal midline, and lateralization patterns were compared with the extent of paranasal pathology. Results: There were 44 participants (M:F=26:18), age 19 to 63 years (average 51). The cohort included 39 patients with sinusitis, affecting the frontal and/or maxillary sinus(es), as well as 5 controls without evidence of paranasal disease. There was a match between the extent of paranasal disease and the results of all 3 Weber test frequencies in 35 patients (80%). Omission of the 2048 and 1024 Hz tuning forks from the analysis yielded a match in 40 (91%) and 43 (98%) patients, respectively. No Weber test lateralized to the nondiseased sinus in any subject. Weber test lateralization was observed in 11% of patients, after the sinonasal pathology was successfully addressed. Conclusion: Weber test lateralization in the absence of aural pathology may be explained by asymmetry related to paranasal disease and may alert to its presence.